Implementation Of Lean Management In Improving The Quality Of Hospital Services: Literature Review - Rooslanda, Elfrida; Ayuningtyas, Dumilah (International Journal Labs, 2023)
Hospitals as labour-intensive and capital-intensive organizations, as well as providing medical and non-medical services require management to increase the efficiency and effectiveness of resources. However, this management must still pay attention to the quality of health services according to service standards and provide benefits for patients. Through Lean Management, continuous improvement can be made by eliminating waste, increasing added value, especially for patients. This is so that the hospital can be the choice of patients to entrust their health. This research is to determine efforts to improve the quality of hospital services using the lean management method. In collecting and synthesizing previous information, this study uses a systematic library research search approach using the PRISMA method. Searches were performed on the Google Scholar and PubMed databases. Articles are limited from 2018-2023, in hospital services and using the Lean Management method. Based on the search results found 1202 articles with 8 copies. From the results of the screening of articles over the last 5 years, 48 ??research titles and abstracts were obtained, then a screening was carried out on the completeness of the selected articles and studies that carried out the process of improving service quality from the results of the Lean Management approach. Efforts to improve quality using the Lean Management method are focused on increasing Value Added activities by reducing Non Value Added activities. Lean Management is considered effective in efforts to improve quality by maximizing existing resources. Through a number of studies obtained, hospitals that implement Lean Management benefit by identifying sources of waste. So that it can be input for the Hospital to focus on efforts to improve these units by reducing waste and increasing VAR (Value Added Ratio), so as to create quality services that meet patient expectations.